The effects of the block exemption regulation reform on the Swiss car market - Nina Leheyda; Patrick Beschorner; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
In 2002, the Swiss Competition Commission (COMCO) introduced a Notice on the Competitive Treatment of Vertical Restraints in Automobile Trade ('Car Notice'). The objective of the Car Notice has been to strengthen competition in the Swiss car market, in particular by avoiding price-fixing practices and market foreclosure and stimulating intrabrand competition in the market for new car sales and competition in the service market. Based on a survey conducted among Swiss car market players, we find that the Car Notice only had a slight impact on competition in the Swiss car market. Although some changes have been identified, they typically cannot solely be explained by the impact of the Car Notice but rather result from general market developments that have led to stronger competition in Switzerland.
urn:nbn:de:bsz:180-madoc-31856
Keywords: K21; L42; L62; 330; vertical agreements; automobile market; multibranding; intrabrand competition; interbrand competition; ex-post evaluation of competition policy